2021
DOI: 10.1080/21507740.2021.1904044
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Self-Trust in DBS Patients

Abstract: Schönau et al. (2021) provides essential concepts and methodological tools for examining the complex interactions that emerge between neurotechnology and an individual's agency. The authors describe the agency dimension of trust as an individual's trust in themselves to make use of feedback provided by neurological interventions in order to effectively evaluate their own experience and choose how to act within their environments. Their discussion is restricted to issues of sensory feedback for those using brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…After examining the scores on different subscales, this study found a nuanced understanding of interoceptive awareness, where the “Trusting” subscale, where individuals trust their internal sensations, showed the highest mean score (63.3% of the maximum attainable score). Therefore, self-trust is found to be important to understand how individuals may interpret and respond to any interoceptive stimuli [ 44 ], where self-trust is a crucial prerequisite for both personal independence and self-esteem [ 45 ], and it shows how individuals reflect and interpret their emotional response [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…After examining the scores on different subscales, this study found a nuanced understanding of interoceptive awareness, where the “Trusting” subscale, where individuals trust their internal sensations, showed the highest mean score (63.3% of the maximum attainable score). Therefore, self-trust is found to be important to understand how individuals may interpret and respond to any interoceptive stimuli [ 44 ], where self-trust is a crucial prerequisite for both personal independence and self-esteem [ 45 ], and it shows how individuals reflect and interpret their emotional response [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation, Walton, 2021). Conversely, distrust in oneself can produce a measurable syndrome in which external information is privileged over one's own memories (Gudjonssen, 2017).…”
Section: Inter/intrapersonal Psychologymentioning
confidence: 99%

Toward A Multiscale Account of Trust

Jinich-Diamant,
Reggente,
Bolis
et al. 2024
Preprint